2020
DOI: 10.3390/ani10081252
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Dietary Humic Preparations on the Content of Essential and Non-Essential Chemical Elements in Hen Eggs

Abstract: This study was conducted to determine the effect of dietary supplementation with two humic preparations, Humokarbowit (HKW) and Humobentofet (HBF), on the mineral content of the albumen and egg yolk of Lohmann Brown hens. The content of macroelements (Ca, K, Mg, Na, P, S), microelements (Al, Ba, Cu, Fe, I, Mn, Si, Sr, Zn) and trace elements (Ag, As, Be, Bi, Cd, Co, Cr, Ga, Hg, Li, Mo, Ni, Pb, Rb, Sb, Se, Sn, Ti, Tl, V, W, Y and Zr) in the feed mixture (FM), albumen and yolk were presented. The material was col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…The obtained results can be compared with those of the tests (38 elements) carried out on the eggs of LB battery-raised hens fed with a standard feed mixture [6]. In the case of GLP in the egg albumen, the concentration of Ca, Cu, Fe, and Na was much higher among macro-and microelements, while Al and K was lower.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The obtained results can be compared with those of the tests (38 elements) carried out on the eggs of LB battery-raised hens fed with a standard feed mixture [6]. In the case of GLP in the egg albumen, the concentration of Ca, Cu, Fe, and Na was much higher among macro-and microelements, while Al and K was lower.…”
Section: Discussionmentioning
confidence: 96%
“…They are a good source of nutraceuticals used in the prevention of civilization diseases [1][2][3]. The chemical composition of eggs is complex and may be influenced by various factors (breed, age of birds, housing system, and feed composition) [4][5][6]. The mineral composition of eggs is important in terms of food safety, due to the fact that all elements, including essential, can become toxic or lead to deficiencies if consumed in inappropriate amounts [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, inorganic elements that are necessary for the proper functioning of the body, as well as heavy metals, can become harmful to the human body by receiving them in high doses or in low, but for a long period [16], [33]. It has been proven [5] that the introduction of such elements as silver, barium, beryllium, bismuth, cobalt, iron, gallium, mercury, potassium, magnesium, nickel, sulphur, antimony, silicon, zinc and zirconium into the diet of chickens causes increase in eggs of the following elements: bismuth, cobalt, nickel, sulphur, iron, potassium, antimony. When iodine is added to the diet of laying hens, the high content of the element in eggs is noted [31],…”
Section: Introductionmentioning
confidence: 99%
“…Japanese quails are a promising species with excellent meat quality traits, high edible meat yield from breast and thighs and optimum meat composition from dietetic point of view. 1 Report by Dobrzański et al 2 showed that quail meat and eggs are renowned for their high quality protein, high biological value and low caloric content, making it a choice product for hypertension prone individuals (Table 1). These birds are mainly produced for their meat and eggs but are also used as laboratory animals because of their small size and require little cage space for rearing.…”
Section: Introductionmentioning
confidence: 99%